Studi Etnografi: Makna Biaya dalam Tradisi Sadeka Ponan di Desa Poto - Kamilatuzzahirah, Siti Alifany; Jumaidi, Lalu Takdir (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
This research was purposed to find out the meaning of cost in Sadeka Ponan Tradition. The research was conducted in Poto Village, Moyo Hilir Sub-district, Sumbawa Regency using a qualitative method of ethnographic approach with an interpretive paradigm. Data were collected by interviewing sources or informants and processed using Spradley's ethnographic approach. The Sadeka Ponan tradition is a tradition carried out annually by the people of Poto Village after the planting season (rice) as a form of gratitude and hope that the plants can be fertile and the results are abundant. There are two concepts of the meaning of costs in this tradition, namely the concept of matching non-profit organizations and the concept of matching business. In the concept of matching non-profit, the meaning of costs in this tradition is as a form of sadeka or charity, batompok ke ina kemina or gathering with relatives, conflict resolution, bearer of blessings, reseki or sustenance. While in the concept of business matching, this tradition is expected to be able to become a tourism object that becomes a forum for income for Poto Village residents. This research is expected to be able to provide renewal in interpreting costs in a culture but still with an in-depth view of accounting principles.